Planejamento operacional para aquisição de dados sismicos em bacias sedimentares brasileiras - Arrais, Tiago Alerrandro Paulino (Universidade Federal Rural do Semi-Árido, 2018)
The advent of the modern society brings with it an ever-increasing demand for energy which is the driving force behind much of the most diverse segments of industries. Oil has long been a major source of energy and raw materials contributing intensely to such purposes, its exploration dates back to ancient times where it still depended on chance to find it. The growing demand for oil makes it increasingly necessary to be accurate as to the location of an accumulation of hydrocarbons in view of the high costs and risks of drilling a well. Researches in the field of oil prospecting have been developed worldwide so that the currently seismic methods employed are quite accurate in locating new deposits. Something as important as the prospecting itself is the operational planning that precedes and fits the prospecting campaign. The present study aimed to qualitatively analyze the reports prepared by two companies in the segment of seismic prospecting by reflection on the operational planning for data acquisition in Brazilian sedimentary basins in order to generate knowledge of this important area of the oil industry. The study consisted in knowing and analyzing all the steps of the operational planning of seismic campaigns. From the analysis performed in the reports it was observed that there is a strong correlation between the aspects considered by both companies, and they are related in three main aspects: costs, safety and legal aspects. Thus, the operational planning phase for the acquisition of seismic data is fundamental importance for the success of the operation, as well as for environmental protection of the areas where operations occur, safety of the teams involved and control of expenses.
Monografia
Keywords: Prospecção sísmica; Petróleo; Planejamento; Seismic prospecting; Petroleum; Planning; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA